Mengembangkan Format Penilaian Komprehensif dalam Pengembangan KTSP - Muhamad Nurhalim (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2018)
Abstract: Logical consequence enactment Permendiknas No. 22, 23, and 24 in 2006 and Government Regulation (PP), No. 19 in 2005 was the management curriculum is left entirely to each the education unit which includes covering the development, implemntation to the evaluation. In management, it is expected every Education Unit able to integrate the development, implementation and evaluation in accordance with the principles of valuation. In the field of development and implementation, in implicit regulation orders to accommodate either three domains of cognitive, effective, psychomotor which is comprehensive and continous. But on the other hand, policy evaluation and rating system specified is not relevant to the demands that were ordered. Therefore, this paper tries to describe the format of assesment in accordance with the principles of the development, implementation and assesment principles in the curriculum or the Education Unit as outlined in Permendiknas and the Government Regulation (PP). Keywords: Format, Evaluation, Curriculum, Development, Implementation, and Education.